Lectura Pictográfica en el desarrollo de la Inteligencia lingüística en los niños y niñas del primer año de educación básica paralelo “c” de la escuela estados Unidos de Norteamérica, cantón Quito, provincia Pichincha, en el año lectivo 2015 – 2016. - Espinel Peñafiel, Marcela Alexandra (2017)
The research called: Pictographic reading in the development of linguistic intelligence in boys and girls of First Year of Basic Education class "C" at United States of America high school, Quito county, Pichincha Province, in the school year 2015-2016, was raised with the aim of generating reading processes using pictograms as teaching learning in the development of linguistic intelligence tools in boys and girls of First Year Basic Education. For the effect begins with the philosophical, epistemological, pedagogical, psychological and legal foundation, next it was realized the theoretical framework analysis corresponding to the independent variable the pictographic reading with its steps, kind of reading, pictographic classification and reading; the dependent variable correspond the development of linguistic intelligence which reference is made to the linguistic profiles and strategies. The methodology focuses on the no experimental design and qualitative while the type of research is applied, descriptive, laboratory and bibliographical, applied deductive method, observation technique supporting in the observation file as an instrument support. As an alternative guideline, the elaboration and application of a didactic guide with activities related to tales, and songs, which guide the work of teachers, based on the research requirements, for correct use of pictographic reading techniques in order to improve linguistic intelligence. In the analysis of results the information acquired from the observation was processed to the boys and girls, statistical tables and graphs were prepared to be analyzed and interpreted according to the percentage reached, finally realized the hypothesis testing, conclusions and recommendations. With the application of pictographic strategies it was possible to show that infants have a greater approach to school because they play, participate, dialogue and communicate with most confidence between the educative community, achieving a better school adjustment, fundamental aspect to strengthen the teaching work and continue with greater dedication guiding new processes of reading through images and symbols, fundamental factor so that in later grades they do not have difficulties in the linguistic development and of the process of the literacy.